Jihat Ammah: Redefinition of Assets in Islamic Boarding Schools Accounting Framework - Binti Shofiatul Jannah; M. Luthfillah Habibi; Mochammad Ilyas Junjunan; Ratna Anggraini Aripratiwi (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
Most of study “stuck” on pragmatic level, they have grasped the Islamic boarding school possessing same character with non-profit entity. As a result, all of the accounting concepts have the same “taste” as modern accounting. In particular, asset definition in Islamic Boarding Schools Accounting Guidelines inclined provides same meaning with it. By looking at the nature of Islamic Boarding Schools beyond non-profit entities, this study aims to, first, conduct a “power” review of assets in the Islamic Boarding School Accounting Guidelines through a critical perspective. Second, re-determining definition of Islamic boarding schools asset based on Al-Quran and Kitab Kuning. Through postmodernist aqidah methodology, the research methods used are literature studies, extracting the nature of pesantren through the Kitab Kuning, and in-depth interviews with informants. Extraction of the definition of assets refers to the Qur'an to obtain depth of analysis. Finally, this study re-proposes a definition of Islamic Boarding Schools assets that goes beyond modern accounting in which pesantren assets are classified as Jihat Ammah.